Response of composite and steel V-structures to localised air blast loading-numerical and experimental - Shekhar, Vinay Ramaswami (Department of Chemical Engineering, 2026)
This research investigated the blast performance of Glass-Fibre Reinforced Polymer (GFRP) Vstructures compared to equivalent mass steel V-structures. The blast performance was measured in terms of three metrics, namely, impulse transferred, maximum mid-point deflection and permanent damage/deformation. A series of blast experiments were performed on manufactured GFRP and steel V-structures. The GFRP V-structures were made using Vacuum Infusion (VI), using a 400 g m−2 woven E-glass and a Prime 20LV resin with a Low Viscosity (LV) slow hardener. The steel V-structures were manufactured by laser cutting the flat panel profiles from a sheet of 2 mm thick DOMEX-700 MC sheet and then Computer Numerical Control (CNC) bending them to the desired profile. Three panel configurations were experimentally blast tested, namely, a 105° V-angle with a 32 mm V-tip radius, a 105° V-angle with a 62 mm V-tip radius and a 120° V-angle with a 32 mm V-tip radius. Blast tests were performed by detonating PE4 charges ranging from 10 g to 40 g at a Stand-Off Distance (SOD) of 34 mm. Digital Image Correlation (DIC) was used to track the transient deformation of the V-structures, while the final deformed profile of the V-structures was determined using a 3D scanner. A series of numerical simulations were also performed on the GFRP and steel V-structures. The simulations used quarter symmetry models to utilise the symmetry of the experimental setup. The material model parameters were obtained from a series of material tests carried out on GFRP and steel specimens. The simulations were validated against the experimental results for a number of test cases for impulse transfer, and transient and permanent deformation. The simulations were then extended to look at a range of V-tip radii, V-angles and charge masses, while the SOD was held constant. For the steel V-structures, the blast experiments found that increasing the V-tip radius and Vangle resulted in an increase in impulse transferred as well as transient and permanent mid-point deflection. This result was confirmed when the set of V-tip radii investigated was increased in the simulations. The trends in the results for the GFRP V-structures were similar to the equivalent steel plates. The delamination and total crack length were observed to increase with an increase in V-angle and charge mass. In general, the study found that GFRP V-structures were inferior to their equivalent mass steel V-structures in terms of panel rupture threshold. The GFRP V-structures exhibited lower transient deformation, but panel rupture on the rear face was observed at a lower charge mass. No tearing or rupture was observed in the steel V-structures tested at similar charge masses.